2013
DOI: 10.1177/0897190013493806
|View full text |Cite
|
Sign up to set email alerts
|

Role of Illness Perceptions and Medication Beliefs on Medication Compliance of Elderly Hypertensive Cohorts

Abstract: The findings provide practical basis for designing interventions and programs aimed at compliance building in elderly populations having hypertension by incorporating the value and importance of patient perceptions of illness and medications in order to achieve desired patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
46
2
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 13 publications
5
46
2
4
Order By: Relevance
“…The current study also found that stronger beliefs about the necessity of antihypertensive medications were related to higher medication adherence; other studies, including those involving Arab populations, have reported similar results. 2,14 No relationship was found between concerns about antihypertensive medications and medication adherence in the present study; this is inconsistent with the findings of previous research. 2,14 In the current study, subjects seemed more anxious about becoming overly dependent on their medications.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…The current study also found that stronger beliefs about the necessity of antihypertensive medications were related to higher medication adherence; other studies, including those involving Arab populations, have reported similar results. 2,14 No relationship was found between concerns about antihypertensive medications and medication adherence in the present study; this is inconsistent with the findings of previous research. 2,14 In the current study, subjects seemed more anxious about becoming overly dependent on their medications.…”
Section: Discussioncontrasting
confidence: 57%
“…2,14 No relationship was found between concerns about antihypertensive medications and medication adherence in the present study; this is inconsistent with the findings of previous research. 2,14 In the current study, subjects seemed more anxious about becoming overly dependent on their medications. It is likely that the low adherence level noted among patients with more concerns about their medications could be improved by addressing these fears when developing a plan of care, particularly with major concerns related to the longterm consequences or side-effects of the medication or fears of dependency.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…We found that improved medication adherence after CHEP was positively associated with improved medication self-efficacy (MASES-R) and with a reduction of concerns about medications as measured by the BMQ. It is unlikely that changes in these underlying determinants of adherence to hypertension treatment [42]- [49] would have occurred without the educational intervention. More patients had begun to engage in moderate physical activity during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Eliciting beliefs using the BMQ, IPQ and MHLCS better predicted adherence as measured by MARS when compared to studies using the BMQ and IPQ 168,185,322 or the BMQ and MHLCS. 134 These two interaction effects suggest that there are important differences in the way beliefs associate with medication adherence, which bivariate analyses are not able to detect.…”
mentioning
confidence: 96%